2018
DOI: 10.1186/s12885-018-4767-x
|View full text |Cite
|
Sign up to set email alerts
|

Could local surgery improve survival in de novo stage IV breast cancer?

Abstract: BackgroundResection of the primary tumor is recommended for symptom relief in de novo stage IV breast cancer. We explored whether local surgery could provide a survival benefit in these patients and attempted to characterize the population that could benefit from surgery.MethodsMetastatic Breast cancer patients (N = 313) with intact primary tumor between January 2006 and April 2013 were separated into two groups according to whether or not they had undergone surgery. The difference in characteristics between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…In previous studies, it was reported that negative margins, bone-only metastasis and systemic therapy were the favorable independent factors for survival, while positive margins, overexpression of HER2/neu and visceral metastasis were the adverse prognostic factors. 7,19,20 In this study, patients with ER and PR positive tumors had better prognosis. ER and PR status were independent prognostic factors, suggesting that tumor biology plays an important role in overall survival.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In previous studies, it was reported that negative margins, bone-only metastasis and systemic therapy were the favorable independent factors for survival, while positive margins, overexpression of HER2/neu and visceral metastasis were the adverse prognostic factors. 7,19,20 In this study, patients with ER and PR positive tumors had better prognosis. ER and PR status were independent prognostic factors, suggesting that tumor biology plays an important role in overall survival.…”
Section: Discussionmentioning
confidence: 53%
“…5,6 However, recent retrospective clinical studies have shown a positive impact on local control and overall survival in newly diagnosed stage IV breast cancer patients after primary site tumor resection. [7][8][9] Conversely, some studies have shown that surgery for metastatic breast cancer does not translate into survival benefits. 10,11 However, these retrospective studies were influenced by the selection bias, because they mainly included younger patients or with single metastatic lesion, only the bone or soft tissue metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published multicentric retrospective study in France indicated that locoregional treatment improved overall survival in breast cancer patients with synchronous metastasis, especially in patients with the molecular subtype of HR-positive/HER2-negative and HER2positive (27). Another retrospective study in Chinese patients showed that surgical removal of the primary tumor could improve the prognosis of patients with bone metastasis alone (28). Importantly, surgery can offer solid pathological evidence for molecular classification, can alleviate clinical symptoms and can reduce tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…The role of surgery in survival is consistent with the conclusions of previous studies. 7,[14][15][16][17] Furthermore, patients with only one symptom had better OS than those with more than one symptom (p = 0.0175). Considering all above results, we can boldly speculate that de novo stage IV BC patients who received surgery are less likely to occur LPRS.…”
Section: Discussionmentioning
confidence: 97%